Das Lokalklima des Mbapit (Kamerun) und sein Einfluss auf die Vegetation - Schramm, Josef (ERDKUNDE, 1958)
The mountain block of the Mbapit rises in the middle of the Bamum highland in the West Cameroons. Whereas arable cultivation is practised in the Bamum highland, the Mbapit mountains are exclusively devoted to animal husbandry. The reason lies in the difference of their vegetation which in turn can only be explained by the special characteristics of the local climate. The diurnal range of temperature as well as the amount of rainfall are greater in the Mbapit than in the Bamum. Local winds, and in particular cloud formation, also differ in the mountains. Three storeys of climate and thus also of local vegetation can be distinguished. First, up to 1500 m.: valley fog with scrub and in parts hard types of grasses. Second, from 1500 m. to 1700 m.: the middle cloud layer with park type land and ideal grazing conditions. Third, above 1700 m.: upper cloud layer with grassland. The Mbapit has been settled since 1905. It is inhabited by about 70 people of the Bororo tribe who live on something like over 600 head of cattle and about 200 sheep and goats; arable cultivation is completely lacking.